The factors of financial performance of SMEs (case of Vietnam) - Hieu Minh Vu; Hieu Tran Chi (Contemporary Economics, 2022)
In the present environment, innovation is now treated as a prime source to earn a competitive edge in the market. Moreover, from a theoretical perspective, the emerging trend towards public relations can also be seen in the prior literature, which adds value to the firm's financial performance. Along with these practices, recent statistics in the literature showed concern towards the complimentary issue; investment strategies and their impact on firms' financial performance. Therefore, seeking to extend research by exploring these three constructs altogether, the study attempts to scrutinize the impact of public relations, innovation practices, and investment strategies on SMEs' financial performance in the context of Vietnam. Authors employ both quantitative approaches with primary data to explore subjects and gain insightful information. The primary data has been gathered from the survey with business owners, managers, and officers in 202 SMEs. The results indicate that public relations, innovation, and investment practices have a positive association with SME.s financial performance. The theme of results concludes that public relations are expected in the future virtue to search for the appropriate practices adapting with the digital transformation of media and communication, wherein SMEs ought to have digital literacy and comprehensive knowledge of public relations practices. This also study contributes to the existing literature to both theoretical and managerial approaches for better awareness of public relations, innovation, and investment practice in the research industry setting.
Keywords: P33; P45; O31; 330; public relations; investment strategies; innovation; financial performance; small and medium-sized enterprises (SMEs)